2018
DOI: 10.4490/algae.2018.33.11.25
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic delimitation of a filamentous marine genus, Capillus gen. nov. (Cyanobacteria, Oscillatoriaceae) with the description of two Brazilian species

Abstract: Lyngbya C. Agardh ex Gomont is a nonheterocytous cyanobacterial genus whose evolutionary history is still poorly known. The traditionally defined Lyngbya has been demonstrated to be polyphyletic, including at least five distinct clades, some of which have been proposed as new genera. Intraspecific diversity is also clearly underestimated in Lyngbya due to the lack of unique morphological characters to differentiate species. In this study, we describe the new genus Capillus T. A. Caires, C. L. Sant'Anna et J. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
0
18
0
2
Order By: Relevance
“…However, with the advent of DNA sequencing and implementation of a polyphasic approach to taxonomic classification, many genera, such as Lyngbya, have been shown to be polyphyletic (Caires et al. 2018a,b, Engene et al. 2012, 2013b, 2018, Komárek et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the advent of DNA sequencing and implementation of a polyphasic approach to taxonomic classification, many genera, such as Lyngbya, have been shown to be polyphyletic (Caires et al. 2018a,b, Engene et al. 2012, 2013b, 2018, Komárek et al.…”
mentioning
confidence: 99%
“…2012, 2013a, 2018, Caires et al. 2018a,b) and the freshwater genera Limnoraphis and Microseira (Komarek et al., 2013, McGregor and Sendall 2015). However, the Lyngbya complex still remains polyphyletic and consists of multiple clades separate from the type species, L. confervoides , that require revision.…”
mentioning
confidence: 99%
“…For the other Brazil's regions, the following studies are reported: South -Coutinho et al [66] for Santa Catarina state, and Garcia-Baptista & Baptista [67] for Rio Grande do Sul state; and Northeast -Nogueira and Ferreira-Correia [68] for Maranhão, Branco et al [69] for Pernambuco, and Caires et al [10,40,41] for Bahia. Additionally, Caires et al [70] Since the first published research about Brazilian marine benthic cyanobacteria which was carried out almost four decades ago, a limited number of studies was realized in this country (Figure 5). The number of studies and the interval among them demonstrate that the knowledge about the diversity and distribution of cyanobacteria are still incipient, especially when considering the coastal extension of Brazil and the great diversity of favorable habitats for the development of these organisms [41].…”
Section: How Much Is Brazilian Marine Benthic Cyanoflora Known?mentioning
confidence: 99%
“…The taxonomy of this phylum had been largely based on morphological characteristics which were often insufficient to define genera and species (Komárek 2003, Taton et al 2003, 2006, Johansen and Casamatta 2005, Turicchia et al 2009, Genuário et al 2013. Moreover, some morphological characters vary under different conditions, such as colonial formation, cellular size, presence of sheaths, heterocytes and akinetes (Hašler et al 2012, Dvořák et al 2015a, Caires et al 2018. Berrendero et al (2011) found that morphological features of Calothrix changed in the culture condition, making them to look like Tolypothrix.…”
Section: Introductionmentioning
confidence: 99%